Peningkatan Penjualan UMKM Dengan Pelatihan Fotografi Produk Untuk Pedagang Kaki Lima Di Jalan Cerme Cilacap - Wulansari, Nuni; Nurwibowo, Fajar; Yusuf, Dede; Islamiati, Desma; Sukirman (Jurnal Arba - Multidisiplin Pengabdian Masyarakat, 2024)
This service involves lecturers and students at Al-Irsyad Cilacap University (UNAIC) in product photography training for groups of street vendors on Jalan Cerme, Cilacap. This training aims to improve the quality of product photos and visual marketing skills to increase the competitiveness and sales of MSMEs, which according to data can increase purchasing interest by up to 40% and sales by up to 25%. This program is expected to create a positive impact on local economic growth and increase awareness of the importance of visual branding for MSMEs, with the support of data showing that structured training can increase the competitiveness of MSMEs by 30% and contribute to increasing the local economy by up to 15%.